GAMBARAN PENGGUNAAN KB HORMONAL DENGAN SIKLUS MENSTRUASI DI WILAYAH KERJA PUSKESMAS GAMBIRSARI SURAKARTA - Erika Dewi Noorratri; Friskha Maudita Oktaviandini; Maryatun Maryatun (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2022)
Introduction: Hormonal contraception is a type of contraception that contains estrogen and progestron hormones and a combination of both. Types of hormonal contraception consist of pills, injections, implants and one of the side effects of using hormonal contraception is a disruption of the menstrual cycle. Objective: to describe the use of hormonal birth control with the menstrual cycle in the working area of ​​the Surakarta Gambirsari Health Center. Method: Type of quantitative descriptive research. The sampling technique is purposive sampling. The instrument used is a checklist. Results: based on the results of the 3-month injection univariate KB test as many as 95 (26.2%) experienced a change in elongated menstrual cycle> 35 days by 70 (35.5%), implantable family planning with respondents 83 (22.9%) experiencing prolonged menstrual cycles > 35 days 66 (33.3%), 1 month injection KB with respondents 93 (25.6%) also experienced changes in the normal menstrual cycle 23-35 days 52 (39.1%), birth control pills with 92 respondents (25, 3%) the majority experienced a normal menstrual cycle of 23-35 days as many as 62 (66.0%). Conclusion: Most family planning acceptors have normal menstrual cycles. 1 month injection KB acceptors have the majority of normal menstrual cycles. Actors with 3 months injection KB are mostly long menstrual cycles. Most implantable KB acceptors have a long menstrual cycle. Key Words: Hormonal, KB, Menstrual Cycle